Missology Approach to Human Resource Development and Economic Empowerment through the Handicraft Industry at GMIM Jerusalem Kinilow Tomohon Congregation, Lokon Empung Region: Pendekatan Misiologi Terhadap Pengembangan Sumber Daya Manusia dan Pemberdayaan Ekonomi melalui Industri Kerajinan Tangan di Jemaat GMIM Yerusalem Kinilow Tomohon, Wilayah Lokon Empung - Ramli Sarimbangun (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Using a missiological lens, this study investigates the GMIM Yerusalem Kinolow church's involvement in human resource development and the congregation's economic empowerment. The purpose of the study is to investigate how the church combines spiritual and material elements to improve the wellbeing of its members. The study centers on the church's handicraft training program, established to equip the congregation with entrepreneurial skills while reinforcing Christian virtues and values. It includes qualitative approaches, such as observations and interviews. Church members who took part in the program provided data, which was then evaluated to find important themes about social effect, spiritual development, and economic growth. The findings demonstrate how well the church's program enhanced the members' technical proficiency and capacity for entrepreneurship. The training's incorporation of Christian concepts led to participants reporting a greater feeling of accountability, integrity, and discipline. Additionally, the program helped participants develop a feeling of solidarity and community, which aided in their spiritual and financial development. Additionally, the church was instrumental in helping members access new economic prospects, even though there are still obstacles to overcome in terms of increasing market access and integrating technology, especially for senior members. The conversation emphasizes the significance of a comprehensive missiological strategy that takes into account people's material and spiritual concerns. The results imply that by using spiritual teachings to direct economic behavior, the church can effectively serve as a facilitator of socio-economic reform. Nonetheless, additional assistance is required to improve market penetration and technical flexibility. This study adds to the body of knowledge on missiology by illuminating the ways in which churches might uphold their theological purpose while promoting economic empowerment. Additionally, it provides helpful suggestions for enhancing church-based economic initiatives, such as the necessity of outside assistance and specialized training to meet the various demands of the membership